Quantitative fit analysis of acromion fracture plating systems using three-dimensional anatomical modelling - Charilaou, Johan (Department of Surgery, 2020)
Background Displaced acromial fractures are challenging to treat. Complex bony anatomy, variable fracture morphology and limitations of available implants present challenges in achieving favourable surgical outcomes. We determined to what extent currently available scapular and clavicular plating systems are able to provide adequate fixation options. Methods Patients presenting to an urban trauma centre with acromial fractures sustained from blunt trauma between 2012 and 2016 were identified (n = 15, 14M / 1F). The fracture patterns were categorized according to location (Type I = 13%, Type II = 27%, Type III = 60%). Computed Tomography (CT) scans were reconstructed to produce three-dimensional (3D) printed anatomical models on which a quantitative fit analysis was performed. Measurements were performed twice, by five separate observers, with fit graded as anatomical fit (< 2mm), intermediate fit (> 2mm) or no-fit. Results The anterior clavicle 6 hole plate fitted best in 45.7% of cases. Acromial plates only achieved 27.3%. The acromion short plate together with the lateral clavicle short plates performed the best in Type II fractures. An inter-observer intraclass correlation coefficient (ICC) agreement of 0.974 was obtained. Conclusion The available commercial acromial plating system fails to provide adequate congruency and fit for fixation. Clavicular plates were superior alternative implants. 3D printed anatomical models can be used effectively to assist in templating implants preoperatively.